A right to discriminate? : how the case of Boy Scouts of America v. James Dale warped the law of free association - Koppelman, Andrew; Wolff, Tobias Barrington (Yale University Press, 2009)
This title demonstrates that the "right" to discriminate has a long and unpleasant history. Koppelman and Wolff bring together legal history, constitutional theory, and political philosophy to analyze how the law ought to deal with discriminatory private organizations.